Extraction and Characterization of Pectin from Orange Peel - Pokhrel, Shanta; Dahal, Sunita; K.C., Samantha (Journal of Nepal Chemical Society, 2024)
Fruit and vegetable processing waste contributes to around 30% of the total weight of the fruits and vegetables. These wastes can be converted into valuable goods for potential benefits. Therefore, this study was focused on extracting pectin from agricultural waste (orange peels) using two methods: alcohol precipitation and enzymatic extraction. The extracted pectin was compared in terms of various properties. Alcohol precipitation resulted in higher yield percentages (16.99 ± 0.8 % wet; 6.46 ± 1.01 % dry respectively) compared to the enzymatic method (16.84 ± 0.42 % wet; 3.66 ± 0.34 % dry, respectively). FT-IR and XRD spectra indicated the presence of highly methylated semi-crystalline pectin in both methods with potent antioxidant property (40.57%). This research work provides comparative extraction method of pectin from agricultural waste i.e. orange peels which has diverse applications in the food, pharmaceutical industries and biomedical applications.